Pendidikan Jiwa Perspektif Imam al-Ghazali dan Relevansinya terhadap Pendidikan di Indonesia - Salamah Eka Susanti (Lembaga Yasin AlSys, 2025)
Imam Al-Ghazali is one of the major figures in Islamic thought who gave profound attention to the education of the soul as a foundation for shaping students’ moral and spiritual character. Although Al-Ghazali’s thought has been widely examined within the tradition of Islamic education, its relevance to the development of education in Indonesia still needs to be elaborated more systematically. This article aims to examine the concept of education of the soul from Imam Al-Ghazali’s perspective and connect it with the development of education in Indonesia today. This study used a literature review method with a descriptive qualitative approach through an examination of Al-Ghazali’s thought and relevant literature. The results of the study show that education of the soul from Imam Al-Ghazali’s perspective includes tazkiyatun nafs as a process of purifying the soul, takhalli as an effort to empty oneself of negative traits, and tahalli as a process of adorning oneself with noble qualities. This concept emphasizes that education is not only oriented toward intellectual development, but also toward the formation of students’ morals, ethics, and spirituality. The conclusion of this article affirms that Imam Al-Ghazali’s thought has strong relevance as a foundation for developing education curricula in Indonesia that are oriented toward character formation and the strengthening of spiritual values. The implications of this study contribute to the development of a more holistic Islamic education by balancing cognitive, moral, and spiritual aspects in the learning process.